UMA ALTERNATIVA SUSTENTÁVEL PARA A PRODUÇÃO DE BIODIESEL: Cyperus esculentus - Gallina, André Lazarin (2011)
Biodiesel is a true alternative to fossil fuels, particularly diesel, but most of the raw material used in the production of ethanol is soy that is inserted into the human food chain, increasing food prices. With population growth, economic and environmental problems, one should look for alternatives for the production of biodiesel. The main objective of this work is the production and physicochemical characterization of biodiesel weed Cyperus esculentus. The techniques were used to characterize gas chromatography, flash point, thermogravimetric analysis, and accelerated oxidation kinetic tests. The results showed that biodiesel tiririca is better than the soy in some tests as flashpoint and thermal stability, but showed that soy biodiesel is better for the stability of oxidation, can be stored for up to five months without losing biofuel properties and mechanisms of oxidation of soybean biodiesel and nuclear growth of purple tiririca were one-dimensional phase boundary. The study of the socio economic benefit cost of biodiesel production of purple tiririca indicated the viability and sustainability of this process.